Updates in Rhea: SPARQLing biochemical reaction data. Issue Volume 47:Issue D1(2019) (1st October 2018) - Lombardot, Thierry; Morgat, Anne; Axelsen, Kristian B; Aimo, Lucila; Hyka-Nouspikel, Nevila; Niknejad, Anne; Ignatchenko, Alex; Xenarios, Ioannis; Coudert, Elisabeth; Redaschi, Nicole; Bridge, Alan
Abstract: Rhea (http://www.rhea-db.org ) is a comprehensive and non-redundant resource of over 11 000 expert-curated biochemical reactions that uses chemical entities from the ChEBI ontology to represent reaction participants. Originally designed as an annotation vocabulary for the UniProt Knowledgebase (UniProtKB), Rhea also provides reaction data for a range of other core knowledgebases and data repositories including ChEBI and MetaboLights. Here we describe recent developments in Rhea, focusing on a new resource description framework representation of Rhea reaction data and an SPARQL endpoint (https://sparql.rhea-db.org/sparql ) that provides access to it. We demonstrate how federated queries that combine the Rhea SPARQL endpoint and other SPARQL endpoints such as that of UniProt can provide improved metabolite annotation and support integrative analyses that link the metabolome through the proteome to the transcriptome and genome. These developments will significantly boost the utility of Rhea as a means to link chemistry and biology for a more holistic understanding of biological systems and their function in health and disease.